Effects of Using Learning Management Model to Enhance Rational Problem Solving and Mathematical Analysis Based on Digital Learning Ecosystem Grounded in Constructionism Theory for High Vocational Certificate Students - Kompittaya, Munlika; Thongpanit, Phichittra; Jantharajit, Nirat (Rajapark Journal, 2024)
Education in the 21st century is an integration of science and technology resulting in a change that offers the student’s opportunity to develop skills and potential according to their interests without limitations and learning contexts. This research aimed to 1) develop a learning management model, 2) study the effectiveness of a learning management model, and 3) survey the students’ satisfaction with learning through a learning management model. The sample consisted of 39 first-year high vocational certificate students studying in the second semester of the academic year of 2023 at That Phanom College, Nakhon Phanom University, which were selected by purposive sampling. The instruments for conducting this research were 1) the learning management model, 2) lesson plans, 3) the manual for using the model, 4) the test for measuring rational problem solving, 5) the ability assessment form of mathematical analysis, and 6) a questionnaire of the students’ satisfactions toward a learning management model. The statistics for analyzing the data were mean (), percentage, standard deviation (S.D.), and dependent samples t-test. The first finding of this research specified that a learning management model contained five components: 1) principles, 2) purposes, 3) concepts and theories, 4) learning management procedures, and 5) assessments. A learning management process consists of five steps: 1) simulation of the student’s interest, 2) arrangement of learning experience and thinking process; 3) learning management by activities; 4) inspection of learning experience; and 5) learning evaluation. The next finding indicated that after learning through a learning management model, the student’s proficiency in rational problem-solving was significantly higher at a .05 level. Besides, after learning through a learning management model, the student’s proficiency in mathematical analysis was significantly higher at a .05 level as well. The last finding found that the overall image of the student’s satisfaction with the use of a learning management model was at the highest level.